A Retrospective Study of Aimed Patch Testing With Aqueous Nickel Sulfate Hexahydrate at 30% and 15% in Patients With Dermatitis. Issue 4 (July 2018) - Bruze, Magnus; Hindsén, Monica; Mowitz, Martin
Abstract : Background: Sometimes, patients with a history of metal intolerance react negatively or doubtfully to nickel at patch testing. Objective: The aim of the study was to investigate whether aqueous nickel sulfate hexahydrate at 15% and 30% traces more contact allergy than the nickel preparation in the baseline series at 5%. Methods: In the period 1995–2015, more than 800 of 16, 059 patients with a negative or doubtful patch test reaction to the petrolatum preparation of nickel at 5% on the day 3 reading were additionally tested with aqueous nickel at 15% and/or 30%. Conclusions: In this retrospective study with aimed patch testing with aqueous nickel solutions, significantly more ( P < 0.001) contact allergy was obtained as compared with the 5% preparation in petrolatum. The 30% solution was significantly better ( P < 0.001) than the 15% solution. To demonstrate that patch testing with nickel at 15% or 30% is better than the present testing with 5% requires simultaneous testing with the 3 nickel preparations.